Perancangan Alat Monitoring Switch Pada PDG ( Pressure Different Gauge ) Berbasis SMS Dengan Microcontroller Arduino - Anjasmara, Kadek Bintang; Divayana, Yoga; Rahardjo, Pratolo (Majalah Ilmiah Teknologi Elektro; Vol 19 No 1 (2020): (Januari - Juni ) Majalah Ilmiah Teknologi Elektro, 2020)
Abstract— In maintaining the quality of aviation fuel, before being marketed, the aviation fuel must pass through the filtering stage using a filter. The use of filters must be monitored for efficiency by using a PDG (pressure different gauge) instrument. PDG is a measuring device that is equipped with a switch and will be a disconnect when the PDG needle shows a number above 15 psi. However, filter monitoring is only done by looking at the PDG installed on each filter and the switches on the PDG have not been used at all. From this problem, the author conducted research out by designing and building a tool that can monitor switches on the PDG and provide SMS notifications. In its design, the device uses Arduino Uno as a microcontroller with a 12VDC power supply. This device is equipped with GSM SIM900A which functions to send SMS. Based on research, the highest current consumption is 0.18 A and the smallest is 0.11 A. The average time for sending an SMS is 7 seconds. Based on testing the tool can work as expected. With the design and construction of this device, it is expected to help PT. Pertamina DPPU Ngurah Rai to monitoring the performance of filters in realtime so that the replacement of filter elements can be done in a timely manner and maintain the marketed aviation has good quality.